Unequal distribution of 16S mtrRNA at the 2-cell stage regulates cell lineage allocations in mouse embryos. Issue 4 (April 2016) - Zheng, Zhuxia; Li, Hongmei; Zhang, Qinfen; Yang, Lele; Qi, Huayu
Abstract : Cell lineage determination during early embryogenesis has profound effects on adult animal development. Pre-patterning of embryos, such as that of Drosophila and Caenorhabditis elegans, is driven by asymmetrically localized maternal or zygotic factors, including mRNA species and RNA binding proteins. However, it is not clear how mammalian early embryogenesis is regulated and what the early cell fate determinants are. Here we show that, in mouse, mitochondrial ribosomal RNAs (mtrRNAs) are differentially distributed between 2-cell sister blastomeres. This distribution pattern is not related to the overall quantity or activity of mitochondria which appears equal between 2-cell sister blastomeres. Like in lower species, 16S mtrRNA is found to localize in the cytoplasm outside of mitochondria in mouse 2-cell embryos. Alterations of 16S mtrRNA levels in one of the 2-cell sister blastomere via microinjection of either sense or anti-sense RNAs drive its progeny into different cell lineages in blastocyst. These results indicate that mtrRNAs are differentially distributed among embryonic cells at the beginning of embryogenesis in mouse and they are functionally involved in the regulation of cell lineage allocations in blastocyst, suggesting an underlying molecular mechanism that regulates pre-implantation embryogenesis in mouse.